2010
DOI: 10.1089/jwh.2010.2128
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and the Development of Premenstrual Syndrome

Abstract: Background: Moderate to severe premenstrual syndrome (PMS) affects 8%-20% of premenopausal women and causes substantial levels of impairment, but few modifiable risk factors for PMS have been identified. Adiposity may impact risk through the complex interaction of hormonal and neurochemical factors, but it is not known if adiposity increases a woman's risk of developing PMS. We have addressed these issues in a prospective study nested within the Nurses' Health Study 2. Methods: Participants were a subset of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
6
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 30 publications
5
84
6
9
Order By: Relevance
“…A cross-sectional study conducted among 874 women aged 18 to 44 reported that obese women had almost a three-fold increased risk for PMS compare to underweight women [24]. Furthermore, another prospective study conducted among women free from PMS at baseline (n = 1057) and aged 27 to 44-years-old found that obese women at baseline had significantly higher risks of developing PMS over 10 years of follow-up [25]. It is thought that obesity modifies neurotransmitter function through its effect on estrogen and progesterone.…”
Section: All Participants N = 2115 N (%) Non-pms N = 794 N (%) Pms Nmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study conducted among 874 women aged 18 to 44 reported that obese women had almost a three-fold increased risk for PMS compare to underweight women [24]. Furthermore, another prospective study conducted among women free from PMS at baseline (n = 1057) and aged 27 to 44-years-old found that obese women at baseline had significantly higher risks of developing PMS over 10 years of follow-up [25]. It is thought that obesity modifies neurotransmitter function through its effect on estrogen and progesterone.…”
Section: All Participants N = 2115 N (%) Non-pms N = 794 N (%) Pms Nmentioning
confidence: 99%
“…Estrogen enhances serotonin action by increasing its synthesis, transport, reuptake and receptor expression, and postsynaptic responsiveness. Therefore, lower estradiol levels associated with adiposity may lead to impaired serotonin function and contribute to the occurrence of PMS [25].…”
Section: All Participants N = 2115 N (%) Non-pms N = 794 N (%) Pms Nmentioning
confidence: 99%
“…This controversy might be sample size, cultural and socioeconomic differences. Un fortunately, the findings of this study don't support that BMI to be a predictors variable that might affect PMS as more than half from the study sample(61.1 %) reported severe PMS.This results are not supported by Seedhom, (20)who reported that obese women were more likely to have sever PMS thanamong normal weight.Also, Study conducted by Bertone, (21)found that BMI was also positively associated with risk of specific physical and emotional symptoms, including swelling of the extremities, backache, abdominal cramping, diarrhea/constipation, mood swings, and food cravings. This disagreement between our results and other studies might be due to differences in BMI categories, sample size differences, differences in subjects age and educational activity as well as, practicing exercises or not.…”
Section: Discussionmentioning
confidence: 97%
“…PMS and PMDD are undoubtedly multifactorial; at least three clinical subtypes have been recognised Freeman et al, 2011). Risk factors include high body mass index, stress, smoking, and early life emotional and physical abuse (Bertone-Johnson et al, 2010; 4 of progesterone: production increases rapidly following ovulation and remains elevated throughout the luteal phase, before returning to basal levels prior to the onset of menstruation. Progesterone passes readily through the blood brain barrier (Pardridge et al, 1980).…”
Section: Premenstrual Dysphorias Are Extremely Common In Large Survementioning
confidence: 99%